Electric Drive and Control System of CKD6E Hybrid Power Locomotive - HE Liang; YAO Xiao-yang (机车电传动)
CKD6E locomotive, the China’s first developed hybrid power locomotive with energy conservation and environmental protection, was introduced, and electric drive circuit, control system and working methods were illuminated. Key issues and solutions measures of the locomotive development and debugging process were proposed. In addition, hybrid power locomotive features different from the traditional were summarized, and improving countermeasures were proposed.